Preparation method of N-doped graded porous carbon material, graded porous carbon material and application
By using materials such as potassium sodium tartrate and urea, N-doped graded porous carbon materials are prepared, and commercial activated carbons are difficult to adsorb trace amounts of weak hydrophobic organic pollutants, achieving efficient and low-cost water pollutant removal and industrial production.
Patent Information
- Application Number
- CN202411190005.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-31
AI Technical Summary
Commercial activated carbons are difficult to effectively adsorb trace amounts of weak hydrophobic organic pollutants in water, and high-cost activators are required during the preparation process, which limits its large-scale application.
Using potassium sodium tartrate as a carbon source and nitrogen source such as urea, N-doped graded porous carbon materials are jointly prepared, and the graded porous carbon materials with microporous templates are formed through high-temperature carbonization, which eliminates activators and improves adsorption of trace organic pollutants. performance.
It achieves excellent adsorption performance for trace organic pollutants, reduces preparation costs, is easy to industrial production, and is coupled with membrane filtration to achieve ultra-fast water purification speed.
Smart Images

Figure CN119215852A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental functional materials and water treatment, and particularly relates to a preparation method of an N-doped hierarchical porous carbon material, the hierarchical porous carbon material and applications. Background Art
[0002] Adsorption of carbon-based materials is an important means of removing organic pollutants from water. The host-guest interaction between carbon-based materials and organic matter mainly includes the adaptation of carbon pore size to the molecular size of pollutants and the interaction between the two, including hydrophobic interaction, van der Waals force and hydrogen bonding. At present, commercial activated carbon mainly relies on hydrophobic interaction to remove hydrophobic organic pollutants in water, but it has poor affinity for weakly hydrophobic organic matter, and there is also the problem of incompatibility between pore size and molecular size of pollutants. Among the many weakly hydrophobic organic matter, most antibiotic drugs can be ionized on the one hand, thereby having strong intermolecular forces with water molecules; on the other hand, the concentration of such micropollutants in water bodies is generally low, which further increases the difficulty of removing micropollutants in actual water bodies. Summary of the invention
[0003] In order to solve the problem that commercial activated carbon is difficult to effectively adsorb trace weakly hydrophobic organic pollutants in water, the present invention provides a method for preparing N-doped hierarchical porous carbon materials. The hierarchical porous carbon materials prepared by the method have excellent adsorption properties for trace organic pollutants and can be used for the adsorption and removal of micro-pollutants in water. In addition, the method does not require additional physical or chemical activation, has low manufacturing cost, is easy to realize large-scale industrial production, and has good application prospects.
[0004] The present invention also provides an N-doped graded porous carbon material and application thereof.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for preparing an N-doped hierarchical porous carbon material, the preparation method comprising:
[0007] dissolving the microporous self-templated carbon source and the nitrogen source in water to obtain a mixed solution;
[0008] freeze-drying the mixed solution to obtain a mixed material;
[0009] The mixed material is carbonized at high temperature under an inert atmosphere, and the obtained product is washed and dried to obtain a hierarchical porous carbon material;
[0010] Wherein, the microporous self-templated carbon source includes potassium sodium tartrate, and the nitrogen source includes any one of urea, dicyandiamide, ammonium chloride and thiourea.
[0011] Furthermore, the step of dissolving the microporous self-templated carbon source and the nitrogen source in water to obtain a mixed solution specifically comprises:
[0012] Dissolve the microporous self-templated carbon source and the nitrogen source in water at a molar ratio of 1:(0.5-3) to obtain a mixed solution;
[0013] Wherein, the molar concentration of the microporous self-template carbon source in the mixed solution is 50-100 mM.
[0014] Furthermore, freeze-drying the mixed solution to obtain a mixed material specifically comprises:
[0015] The mixed solution is freeze-dried at a freeze-drying temperature of -60 to -40°C for a freeze-drying time of 18 to 36 hours to obtain a mixed material.
[0016] Furthermore, the mixed material is subjected to high temperature carbonization under an inert atmosphere, and the obtained product is washed and dried to obtain a hierarchical porous carbon material, which specifically includes:
[0017] Under an inert atmosphere, the mixture is heated to 600-800° C. at 3-8° C. / min for carbonization, and the heat preservation time is 1-3 hours. The obtained product is washed and vacuum dried to obtain a graded porous carbon material.
[0018] Optionally, the obtained product is washed and vacuum dried to obtain a hierarchical porous carbon material, which specifically comprises:
[0019] The obtained product was washed with water at 60-90° C. for 3-5 times, and then vacuum dried at 60-100° C. for more than 8 hours to obtain a hierarchical porous carbon material.
[0020] Based on the same inventive concept, the present invention provides an N-doped hierarchical porous carbon material, and the hierarchical porous carbon material is prepared by the above-mentioned method for preparing an N-doped hierarchical porous carbon material.
[0021] Based on the same inventive concept, the present invention provides a micro-pollutant adsorption-filtration water treatment material, the water treatment material comprising a microfiltration membrane, the surface of the microfiltration membrane being adsorbed with the above-mentioned N-doped graded porous carbon material;
[0022] The pore size of the microfiltration membrane is 0.22-0.7 μm, and the content of the graded porous carbon material on the surface of the microfiltration membrane is 2-90 mg / cm 2 .
[0023] Based on the same inventive concept, the present invention provides a method for preparing a micro-pollutant adsorption-filtration water treatment material, the preparation method comprising:
[0024] Dispersing the above-mentioned N-doped hierarchical porous carbon material in water, and then filtering the hierarchical porous carbon material to the surface of a microfiltration membrane by vacuum filtration to form a water treatment material;
[0025] The pore size of the microfiltration membrane is 0.22-0.7 μm, and the content of the graded porous carbon material on the surface of the microfiltration membrane is 2-90 mg / cm 2 .
[0026] Based on the same inventive concept, the present invention provides an application of an N-doped hierarchical porous carbon material in adsorbing and / or removing trace organic pollutants in water.
[0027] Based on the same inventive concept, the present invention also provides an application of a micro-pollutant adsorption-filtration water treatment material in adsorbing and / or removing trace organic pollutants in water.
[0028] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0029] 1. The present invention discloses a method for preparing N-doped graded porous carbon materials. The method uses potassium sodium tartrate as a carbon source and potassium sodium tartrate as glucose waste, which is low in price. In the high-temperature carbonization process, potassium sodium carbonate with a microporous template effect is generated. Compared with the preparation of traditional activated carbon, the step of adding activators such as KOH for activation is omitted, thereby greatly reducing the preparation cost. Nitrogen sources such as urea can further regulate the nitrogen doping amount and pore size to form N-doped graded porous carbon. The prepared N-doped graded porous carbon material has a stronger π-π interaction with organic pollutants and has excellent adsorption performance for trace organic pollutants. At the same time, due to its extremely fast adsorption kinetics, it can be coupled with membrane filtration to achieve ultrafast water purification speed, and it is easy to separate powdered carbon materials. The present invention uses a microporous self-template precursor to prepare functionalized carbon materials, without the need for additional physical and chemical activation, with low manufacturing cost and easy operation, easy to achieve large-scale industrial production, and good application prospects.
[0030] 2. The present invention discloses an N-doped hierarchical porous carbon material, which is prepared by one-step high-temperature carbonization of a microporous self-template precursor (i.e., potassium sodium tartrate). The hierarchical porous carbon material has the advantages of high specific surface area, developed pores, and adjustable pore size (by changing the ratio of carbon source to nitrogen source). Through N-doping functionalization, the hierarchical porous carbon material has a stronger π-π interaction force for organic pollutants, and thus has excellent adsorption performance and removal efficiency for low-concentration weakly hydrophobic drug-like new pollutants, and can be used for the adsorption and removal of micropollutants in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 Schematic diagram of the preparation process of N-doped graded porous carbon materials.
[0033] Figure 2 These are scanning electron microscope images of the carbon materials prepared in Examples 1 to 6: (a) to (f) correspond to the carbon materials prepared in Examples 1 to 6, respectively.
[0034] Figure 3 a is the nitrogen adsorption-desorption curve of the carbon materials with different pore size characteristics prepared in Examples 1 to 6.
[0035] Figure 3 b is the pore size distribution diagram of the carbon materials with different pore size characteristics prepared in Examples 1 to 6.
[0036] Figure 4 XPS SN1s spectra of different carbon materials prepared in Examples 1 to 6.
[0037] Figure 5 This is a graph showing the adsorption kinetics of carbamazepine on different carbon materials prepared in Examples 1 to 6.
[0038] Figure 6 This is a schematic diagram of Example 7.
[0039] Figure 7 This is a diagram showing the continuous flow water treatment effect of Example 7. DETAILED DESCRIPTION
[0040] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0041] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0042] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0043] The overall idea of the present invention is as follows:
[0044] At present, among many weakly hydrophobic organic substances, most antibiotic drugs can be ionized on the one hand, thus having strong intermolecular forces with water molecules; on the other hand, the concentration of such micropollutants in water bodies is generally low, which further increases the difficulty of removing micropollutants in actual water bodies. Therefore, functional regulation of porous carbon further enhances the short-range interaction between it and micropollutants, and achieves the best adaptation between it and micropollutants from the two aspects of pore structure adaptation or force enhancement, thereby improving the adsorption distribution coefficient of micropollutants in solid-liquid two phases (porous carbon adsorbent / aqueous solution), which is particularly important for strengthening the adsorption and removal of micropollutants.
[0045] As one of the main short-range forces, the inventors believe that by doping with heteroatoms, the electron cloud distribution on the surface of carbon-based materials can be regulated by utilizing the differences in electronegativity and valence electron structure between heteroatoms and carbon atoms, forming electron-deficient and electron-rich centers on the carbon rings, thereby strengthening the π-π electron interaction between carbon-based materials and organic pollutants. This is a feasible method to enhance the adsorption performance of carbon-based materials for organic pollutants, especially micro-pollutants.
[0046] In addition, the current preparation process of heteroatom-doped porous carbon, such as the preparation process of N-doped porous carbon, mostly uses nitrogen source, carbon source and external activator to prepare porous carbon. However, the addition of activators such as KOH not only easily corrodes the equipment, but also greatly increases the manufacturing cost of porous carbon, making it difficult to apply on a large scale.
[0047] Based on this, the present invention provides a method for preparing N-doped hierarchical porous carbon materials, which uses potassium sodium tartrate as a carbon source, generates potassium sodium carbonate with a microporous template function during the pyrolysis process, and compared with the preparation of traditional activated carbon, the step of adding activators such as KOH for activation is omitted, which greatly reduces the preparation cost. Nitrogen sources such as urea can further regulate the nitrogen doping amount and pore size to form N-doped hierarchical porous carbon. The prepared N-doped hierarchical porous carbon material has a stronger π-π interaction with organic pollutants and has excellent adsorption performance for trace organic pollutants. The method uses microporous self-template precursors to prepare functionalized carbon materials, does not require additional physical and chemical activation, has low manufacturing costs, is easy to operate, and is easy to achieve large-scale industrial production, with good application prospects.
[0048] Specifically, the present invention provides a method for preparing an N-doped hierarchical porous carbon material, comprising:
[0049] S1. dissolving the microporous self-templated carbon source and the nitrogen source in water to obtain a mixed solution;
[0050] S2. freeze-drying the mixture to obtain a mixture;
[0051] S3. The mixture is carbonized at high temperature under an inert atmosphere, and the obtained product is washed and dried to obtain a hierarchical porous carbon material;
[0052] Wherein, the microporous self-template carbon source includes potassium sodium tartrate, and the nitrogen source includes any one of urea, dicyandiamide, ammonium chloride and thiourea.
[0053] In the present invention, potassium sodium tartrate is used as the carbon source, and the potassium sodium carbonate generated in situ during the pyrolysis process is embedded in the carbon material in situ to form a microporous template, which can be easily washed away with hot water, leaving a rich microporous structure. Therefore, the step of using potassium hydroxide and other chemical reagents for activation and pore formation in the traditional activated carbon preparation method is omitted, greatly reducing the preparation cost.
[0054] Step S1 specifically includes:
[0055] Dissolve the microporous self-templated carbon source and the nitrogen source in water at a molar ratio of 1:(0.5-3) to obtain a mixed solution;
[0056] Wherein, the molar concentration of the microporous self-template carbon source in the mixed solution is 50-100 mM.
[0057] In the present invention, the advantage of the microporous self-template carbon source and the nitrogen source being in a molar ratio of 1:(0.5-3) is that in this range, the generated microporous self-template can be fully utilized, the specific surface area of the material can be maximized, and the pore size structure can be adjusted to a range that is more suitable for the adsorption of organic pollutants in the water treatment field.
[0058] In the present invention, the advantage of using the above concentration of the microporous self-templated carbon source in the mixed solution is that the use of solvent water can be minimized while ensuring that the precursor is fully dissolved and mixed evenly, which is beneficial to saving subsequent freeze-drying time.
[0059] Step S2 specifically includes:
[0060] The mixed solution is freeze-dried at a freeze-drying temperature of -60 to -40°C for a freeze-drying time of 18 to 36 hours to obtain a mixed material.
[0061] Step S3 specifically includes:
[0062] Under an inert atmosphere, the mixture is heated to 600-800°C at 3-8°C / min for carbonization, and the insulation time is 1-3h. The obtained product is washed with 60-90°C water for 3-5 times, and then vacuum dried at 60-100°C for more than 8h to obtain a graded porous carbon material.
[0063] In the present invention, the advantage of carbonizing the mixture at 600-800°C is that it can ensure that the potassium sodium carbonate in the precursor is fully mixed and fully carbonized by the self-template, and that N is fully doped. Too low a carbonization temperature will lead to incomplete carbonization, while too high a temperature will lead to excessive graphitization of the carbon material, resulting in a decrease in the N doping amount. The advantage of a heating rate of 3-8°C / min is that it prevents excessive pyrolysis by uniformly heating.
[0064] In the present invention, the carbonized product is washed with water at 60-90° C. This is because potassium carbonate sodium has a high solubility in hot water. Hot water washing can fully remove the generated microporous template - potassium carbonate sodium, avoiding the waste of chemical reagents caused by acid washing.
[0065] Based on the same inventive concept, the present invention also provides a micro-pollutant adsorption-filtration water treatment material, the water treatment material comprising a microfiltration membrane, the surface of the microfiltration membrane being adsorbed with N-doped graded porous carbon material;
[0066] The pore size of the microfiltration membrane is 0.22-0.7 μm, and the content of the graded porous carbon material on the surface of the microfiltration membrane is 2-90 mg / cm 2 .
[0067] In the present invention, the content of graded porous carbon material on the surface of the microfiltration membrane is 2 to 90 mg / cm 2 The advantage is that it can achieve efficient removal of pollutants without significantly reducing the adsorption / filtration flux. The dosage here is flexible and variable. Too little will result in poor pollutant removal, while too much will cause high water filtration pressure.
[0068] Based on the same inventive concept, the present invention also provides a method for preparing a micro-pollutant adsorption-filtration water treatment material, comprising:
[0069] The N-doped graded porous carbon material is dispersed in water, and then the graded porous carbon material is filtered to the surface of a microfiltration membrane by means of reduced pressure filtration to form a water treatment material.
[0070] In the present invention, the advantage of using a reduced pressure filtration method to filter the graded porous carbon material to the surface of the microfiltration membrane is that the powdered carbon can be evenly distributed on the surface of the microfiltration membrane to form a dense adsorption layer.
[0071] The following will describe in detail the preparation method of an N-doped graded porous carbon material, the graded porous carbon material and the application of the present application in combination with embodiments and experimental data.
[0072] Example 1
[0073] This embodiment provides a method for preparing an N-doped hierarchical porous carbon material. Figure 1 As shown, the specific steps are as follows:
[0074] (1) 2.83 g of potassium sodium tartrate tetrahydrate and 1.2 g of urea were mixed and dissolved in 20 mL of water, where the molar ratio of potassium sodium tartrate to urea was 1:2, and then freeze-dried at -60°C for 24 hours;
[0075] (2) The freeze-dried mixture is placed in a tubular furnace, and under argon protection, the temperature is increased to 700° C. at a heating rate of 5° C. / min and kept at this temperature for 2 hours for high-temperature carbonization.
[0076] (3) The obtained carbonized material was washed with 80°C hot water for 3-5 times and dried in a vacuum oven at 70°C for 12 h to obtain an N-doped hierarchical porous carbon material, named NC2.
[0077] Example 2
[0078] This embodiment provides a method for preparing an N-doped hierarchical porous carbon material, which differs from Example 1 only in that the amount of urea is changed to 0 g and the freeze-drying step is omitted, and the other steps and conditions are referred to Example 1. The obtained material is named NCO.
[0079] Example 3
[0080] This embodiment provides a method for preparing an N-doped hierarchical porous carbon material, which differs from the embodiment 1 only in that the amount of urea is changed to 0.3 g, and the other steps and conditions are the same as those of the embodiment 1. The obtained material is named NC0.5.
[0081] Example 4
[0082] This embodiment provides a method for preparing an N-doped hierarchical porous carbon material, which differs from the embodiment 1 only in that the amount of urea is changed to 0.6 g, and the other steps and conditions are the same as those of the embodiment 1. The obtained material is named NC1.
[0083] Example 5
[0084] This embodiment provides a method for preparing an N-doped hierarchical porous carbon material, which differs from the embodiment 1 only in that the amount of urea is changed to 0.9 g, and the other steps and conditions are the same as those of the embodiment 1. The obtained material is named NC1.5.
[0085] Example 6
[0086] This embodiment provides a method for preparing an N-doped hierarchical porous carbon material, which differs from the embodiment 1 only in that the amount of urea is changed to 1.8 g, and the other steps and conditions are the same as those of the embodiment 1. The obtained material is named NC3.
[0087] Example 7
[0088] This embodiment provides a water treatment unit coupled with N-doped graded porous carbon material and membrane filtration, such as Figure 6 As shown, it is constructed by the following method:
[0089] (1) 25 mg of the N-doped hierarchical porous carbon material prepared in Example 1 was added to 100 mL of deionized water and ultrasonically dispersed uniformly, and then filtered onto a nylon microporous filter membrane with a pore size of 0.22 μm to construct an adsorption layer to form an adsorption-filtration unit;
[0090] (2) The adsorption-filtration unit is placed in a membrane separation device, the water inlet and outlet are connected by a peristaltic pump, and the membrane separation device is connected to the pipeline between the peristaltic pump and the water outlet to perform adsorption-filtration water treatment.
[0091] Example 8
[0092] This example characterizes the carbon materials prepared in Examples 1 to 6.
[0093] 1. The carbon materials prepared in Examples 1 to 6 were characterized using a scanning electron microscope. The results are as follows: Figure 2 shown.
[0094] From the scanning electron microscope image, it can be seen that the NC0 obtained by direct carbonization of potassium sodium tartrate has an irregular block structure with micron-scale discontinuous connections, indicating that the nanoscale NaKCO3 crystals formed during the carbonization process will gradually grow and aggregate to the micron level, and water washing causes the complete block structure to break into irregular shapes. With the increase of the urea ratio in the precursor, the nitrogen-doped hierarchical porous carbon gradually approaches the formation of a sheet structure, which may be due to the formation of an intermediate with a two-dimensional lamellar structure during the pyrolysis of urea, thereby guiding the carbonization of NCx along the lamellar contour.
[0095] 2. The nitrogen adsorption-desorption curves and pore size distribution of the carbon materials prepared in Examples 1 to 6 were tested using a pore size and specific surface area analyzer. The results are as follows: Figure 3 shown.
[0096] Depend on Figure 3a It can be seen that the amount of N2 adsorbed by NC0 in the low-pressure zone (relative pressure <0.1) increases sharply with the increase of relative pressure, and then the adsorption amount remains almost unchanged, which is consistent with the characteristics of type I adsorption isotherm, indicating that NC0 is mainly microporous. The N2 adsorption trend of the other N-doped porous carbon materials in the low-pressure zone is similar to that of NC0, while in the medium-pressure zone (P / P0 is 0.1~0.4), the N2 adsorption amount further increases with the increase of relative pressure, and finally reaches the highest when P / P0 is 1. Its adsorption isotherm has the characteristics of both type I and type IV adsorption isotherms and there is an H4 type hysteresis loop, which indicates that the addition of urea can play a role in pore expansion, thereby leading to the formation of a microporous-mesoporous-macroporous hierarchical porous structure in NCx. In addition, NC0 has a pure microporous structure (<2nm), while the pore size distribution peaks of NC0.5~NC3 gradually shift to the right, and a small proportion of pore size distribution peaks appear around 50nm, and the peak intensity increases successively ( Figure 3 b). It shows that with the increase of urea ratio in the precursor, the pore size of NCx increases from less than 2 nm of NC0 to 6.8 nm of NC3, forming a hierarchical porous structure. The specific surface area of the nitrogen-doped hierarchical porous carbon materials is ranked as follows: NC3 (1629 nm 2 / g) <NC(1786m 2 / g) <NC0.5(1787m 2 / g) <NC1(2004m 2 / g) <NC1.5(2051m 2 / g) <NC2(2114m 2 / g).
[0097] 3. The carbon materials prepared in Examples 1 to 6 were characterized using an X-ray photoelectron spectrometer. The results are as follows: Figure 4 shown.
[0098] The high-resolution XPS spectra of N1s of N-doped hierarchical porous carbon materials were analyzed, such as Figure 4 As shown, the N 1s spectrum can be divided into four forms of N after deconvolution, and the binding energies from low to high correspond to pyridinic nitrogen (398.2 eV), pyrrolic nitrogen (399.9 eV), graphitic nitrogen (402.0 eV) and oxidized nitrogen (405.1 eV), indicating successful N doping.
[0099] Example 9
[0100] This example tests the adsorption performance of the carbon materials prepared in Examples 1 to 6.
[0101] 1. Adsorption capacity test of different N-doped graded porous carbon materials
[0102] Carbamazepine (CBZ) was selected as the target pollutant, and a 50 mg / L carbamazepine solution was prepared. The static adsorption method was used, and the porous carbon materials prepared in Examples 1-6 were used as adsorbents, with a dosage of 0.2 g / L. The adsorption results are as follows Figure 5 shown. The adsorption capacity of NCx exceeded 220 mg / g, which was greater than that of the micro-porous carbon NC0 without N doping (139.6 mg / g). Moreover, the adsorption rate increased successively with the increase in the pore size of NCx, following the order: NC0 < NC0.5 < NC1 < NC1.5 < NC2. When the pore size continued to increase to NC3 (6.8 nm, 42%), the k2 value decreased instead. This was mainly because the amount of micropores in NC3 was insufficient and the specific surface area decreased, resulting in the pollutants enriched in the mesoporous channels of NC3 being unable to reach the adsorption sites in the micropores quickly, thus causing a decrease in the adsorption rate, but still higher than that of NC0. When NC2 reached the adsorption end point, its adsorption capacity and initial adsorption rate for CBZ were 1.78 times and 30 times that of NC0, respectively.
[0103] 2. Performance test of the water treatment of the adsorption - filtration unit formed by coupling NC2 with membrane filtration
[0104] As shown in Example 7 and Figure 6 shown, a water treatment unit was constructed by coupling NC2 with a microfiltration membrane, and its effective filtration area was 25 mg / 12.4 cm 2 . Using carbamazepine (CBZ) as the target pollutant, the concentration of CBZ in the influent was set at 1 mM, the peristaltic pump was started, and the influent rate was 4 mL / min for adsorption - filtration water treatment.
[0105] The results of continuous - flow water treatment are as follows Figure 7 shown. The results show that under the single - filtration condition, the removal rate of CBZ by the water treatment unit exceeded 97%, and the water production reached 10 L.
[0106] Finally, it should also be noted that the term "comprises", "comprising", or any other variation thereof is intended to cover a non - exclusive inclusion, such that a process, method, article, or apparatus that comprises a series of elements includes not only those elements but also other elements not expressly listed, or elements that are inherent to such process, method, article, or apparatus.
[0107] Although the preferred embodiments of the present invention have been described, those skilled in the art can make additional changes and modifications once they learn the basic creative concept. Therefore, the appended claims are intended to be construed as including the preferred embodiments as well as all changes and modifications falling within the scope of the present invention.
[0108] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing an N-doped hierarchical porous carbon material, characterized in that: The preparation method comprises: dissolving the microporous self-templated carbon source and the nitrogen source in water to obtain a mixed solution; freeze-drying the mixed solution to obtain a mixed material; The mixed material is carbonized at high temperature under an inert atmosphere, and the obtained product is washed and dried to obtain a hierarchical porous carbon material; Wherein, the microporous self-template carbon source includes potassium sodium tartrate, and the nitrogen source includes any one of urea, dicyandiamide, ammonium chloride and thiourea.
2. The method for preparing an N-doped hierarchical porous carbon material according to claim 1, characterized in that: The step of dissolving the microporous self-templated carbon source and the nitrogen source in water to obtain a mixed solution specifically comprises: Dissolve the microporous self-templated carbon source and the nitrogen source in water at a molar ratio of 1:(0.5-3) to obtain a mixed solution; Wherein, the molar concentration of the microporous self-template carbon source in the mixed solution is 50-100 mM.
3. The method for preparing an N-doped hierarchical porous carbon material according to claim 1, characterized in that: The freeze-drying of the mixed solution to obtain a mixed material specifically comprises: The mixed solution is freeze-dried at a freeze-drying temperature of -60 to -40°C for a freeze-drying time of 18 to 36 hours to obtain a mixed material.
4. The method for preparing an N-doped hierarchical porous carbon material according to claim 1, characterized in that: The mixed material is subjected to high temperature carbonization under an inert atmosphere, and the obtained product is washed and dried to obtain a hierarchical porous carbon material, which specifically comprises: Under an inert atmosphere, the mixture is heated to 600-800° C. at 3-8° C. / min for carbonization, and the heat preservation time is 1-3 hours. The obtained product is washed and vacuum dried to obtain a graded porous carbon material.
5. The method for preparing an N-doped hierarchical porous carbon material according to claim 4, characterized in that: The obtained product is washed and vacuum dried to obtain a hierarchical porous carbon material, which specifically comprises: The obtained product was washed with water at 60-90° C. for 3-5 times, and then vacuum dried at 60-100° C. for more than 8 hours to obtain a hierarchical porous carbon material.
6. An N-doped hierarchical porous carbon material, characterized in that: The hierarchical porous carbon material is prepared by the method for preparing an N-doped hierarchical porous carbon material according to any one of claims 1 to 5.
7. A micro-pollutant adsorption-filtration water treatment material, characterized in that: The water treatment material comprises a microfiltration membrane, and the N-doped hierarchical porous carbon material according to claim 6 is adsorbed on the surface of the microfiltration membrane; The pore size of the microfiltration membrane is 0.22-0.7 μm, and the content of the graded porous carbon material on the surface of the microfiltration membrane is 2-90 mg / cm 2 .
8. The method for preparing a micro-pollutant adsorption-filtration water treatment material according to claim 7, characterized in that: The preparation method comprises: Dispersing the N-doped hierarchical porous carbon material according to claim 6 in water, and then filtering the hierarchical porous carbon material to the surface of a microfiltration membrane by vacuum filtration to form a water treatment material; The pore size of the microfiltration membrane is 0.22-0.7 μm, and the content of the graded porous carbon material on the surface of the microfiltration membrane is 2-90 mg / cm 2 .
9. Use of the N-doped hierarchical porous carbon material as claimed in claim 6 in adsorbing and / or removing trace organic pollutants in water.
10. Use of the micro-pollutant adsorption-filtration water treatment material as claimed in claim 7 in adsorbing and / or removing trace organic pollutants in water.